Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004227.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for preventing pre-eclampsia

Abstract: These results should be interpreted with caution, as most of the data come from poor quality studies. Nevertheless, antioxidant supplementation seems to reduce the risk of pre-eclampsia. There also appears to be a reduction in the risk of having a small-for-gestational-age baby associated with antioxidants, although there is an increase in the risk of preterm birth. Several large trials are ongoing, and the results of these are needed before antioxidants can be recommended for clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 32 publications
2
61
1
6
Order By: Relevance
“…This finding is not consistent with the pooled results of the other clinical trials of antioxidant vitamins, which do not suggest a benefit from treatment. 30 Recently, the National Institutes of Health's Maternal-Fetal Medicine Units completed a large trial including several institutions in the United States, which reached a similar conclusion. 31 In addition, detrimental effects of supplemental vitamin C and vitamin E during gestation have been reported.…”
Section: Methodological Considerations and Strengthsmentioning
confidence: 84%
See 2 more Smart Citations
“…This finding is not consistent with the pooled results of the other clinical trials of antioxidant vitamins, which do not suggest a benefit from treatment. 30 Recently, the National Institutes of Health's Maternal-Fetal Medicine Units completed a large trial including several institutions in the United States, which reached a similar conclusion. 31 In addition, detrimental effects of supplemental vitamin C and vitamin E during gestation have been reported.…”
Section: Methodological Considerations and Strengthsmentioning
confidence: 84%
“…31 In addition, detrimental effects of supplemental vitamin C and vitamin E during gestation have been reported. 30 38 39 Limitations of study The intervention used in this study must be evaluated in a population of pregnant women at low risk of preeclampsia. This is particularly relevant because we found a high prevalence of recurrence of pre-eclampsia in the studied population.…”
Section: Methodological Considerations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certaines études ont montré la corrélation positive entre le statut maternel en ces deux vitamines et le poids de naissance [7,8] ; cependant, ces études sont anciennes et de méthodologie différente. Enfin, dans une récente mise à jour de la base de données « Cochrane » [26][27][28] aucune corrélation significative entre la supplémentation en ces vitamines et le poids foetal n'a été démontrée. Nos résultats sont concordants avec ces suggestions.…”
Section: Discussionunclassified
“…These observations have led to trials of the prophylactic effects of antioxidants, including vitamins C and E and selenium. A recent Cochrane review of seven randomized trials [18] reported a 39 % reduction in the risk of pre-eclampsia associated with oral antioxidant supplements. The authors stress that these findings should be interpreted with caution as some data were from poor quality studies.…”
Section: Pathophysiology Of Pre-eclampsiamentioning
confidence: 99%